A peticão inicial: um estudo sociointeracionista da peça jurídica na academia - Fernandes, Cátia Cristina Degan (Universidade do Vale do Rio dos Sinos, 2019)
We know that the appropriation of text genre writing skills is an essential competence for the performance of academic or professional activities. In the field of Law this is by no means any different. It is fundamental, for the full exercise of those activities, to master the text genres related to the legal field and their social practices of reference. Therefore, this paper aims to discuss how the appropriation of petition text genres - and, more specifically, the use of linguistic-discursive operations inherent to it - evidences and potentiates the development of literacy processes by Law students, which in turn, helps them in their insertion in the context of a professional internship. Developed methodologically by a qualitative, interpretative research, this study analyzes the mechanisms of textualization (nominal cohesion, connection and verbal cohesion), from the perspective of Socio-Discursive Interactionism - SDI (BRONCKART, 1999). The intersection between SDI conceptions of text genres (BRONCKART & MACHADO, 2004; SCHNEUWLY & DOLZ, 2004) and academic literacy studies (LEA, STREET, 2014; STREET, 2009) supports the theoretical contributions of this research and endorses the analyzes of the petitions made by the Law students coursing the 8th semester and the ones made by Núcleo de Direito do Trabalho (Department of Labor Law) from a university in a city of Minas Gerais, Brazil. Based on Bronckart's model of textual architecture (1999, 2006), the analyzes focused on the textual-linguistic and discursive dimensions mobilized in the construction of the texts that form the corpus of this research. The results suggest that the organization of the types of theoretical discourse and narration, through the lexicon and grammar (nominal, connective and verbal phrases) cooperate to construct the overall meaning of the petition and assure the argumentativeness/persuasion. Thus, we conclude that this legal piece constitutes a writing practice that, when appropriated, can lead the student from the academic context to the most diverse areas of the professional practice of Law
Keywords: Escrita; Petição inicial; Interacionismo Sociodiscursivo; Letramentos acadêmicos; Writing; Petition; Socio-discursive Interactionism; Academic writing literacy; ACCNPQ::Lingüística, Letras e Artes::Lingüística